EUROPEAN DIMENSION OF NATIONAL PERSONNEL POLICY OF UKRAINE IN TRAINING SPECIALISTS FOR THE SYSTEM OF EDUCATION - Бобрицька, В. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article defines the legal, theoretical and practical background in the implementation of personnel policy of Ukraine to meet modern challenges associated with the integration of the national system of education to the European educational and scientific area; provides interpretation of personnel policy of Ukraine in education as a set of principles, methods of state education authorities’ action for the organization of human resources through the formation, maintenance and development of educational values ​​and ideals, norms, rules and procedures that can ensure the integrity and stability of the system of education according to the state target plants; determines the status of staffing of the education system based on modern monitoring studies of test questions; singles out approaches that will ensure a European dimension in the formation of personnel policy of Ukraine in training specialists for the system of education